Assessing knowledge and awareness about Chlamydia trachomatis among undergraduate students at a University of Technology in KwaZulu-Natal, South Africa - Radebe, Luhle; Jaya, Ziningi; Govender, Kristambal (Student’s Journal of Health Research Africa, 2025)
Background Chlamydia trachomatis (CT) is the leading bacterial cause of sexually transmitted infections (STIs) worldwide and represents a major public health problem. The World Health Organization estimated in 2020 that the global prevalence of CT infections had increased by 2.9%, with women disproportionately affected. Understanding knowledge and awareness levels of CT among young adults is essential to inform prevention strategies. The study aimed to assess the level of knowledge and awareness of CT among undergraduate students at a University of Technology in KwaZulu-Natal, South Africa. Methods A cross-sectional survey was conducted among female students. Data was collected via a self-administered electronic questionnaire consisting of four sections: demographics and practices; awareness and knowledge of STIs; knowledge of CT; and awareness of CT risk factors and screening methods. Descriptive statistics were used to summarize responses. Results Most participants (90%) had heard of STIs, primarily through social media, school, clinics, and community sources. However, only 20% reported ever being tested for an STI. Awareness of CT specifically was low, with only 43% recognizing the infection and its mode of transmission. Furthermore, 83% lacked knowledge of CT prevention and management. Small proportions identified abstinence (7%), testing (11%), and education/awareness campaigns as preventive measures. Conclusion Although general awareness of STIs was high, knowledge of CT was limited. Targeted health education and campus-based interventions are needed to improve awareness, prevention, and screening practices for specific STIs. The study was limited by its small, single-institution sample and reliance on online survey distribution, which may not have fully represented the intended student population.